Integrating electrical heating elements in appliance design - Hegbom, Thor (Electrical engineering and electronics, 1997)
"Offers details on the utilization of electrical heating elements in consumer appliance design and industrial processes. The text includes basic theory, metallurgy and production advice for developing more reliable and cost-effective heaters. It provides tables comparing resistivity and surface resistance of different materials, and listing the resistance and weight per metre as well as surface per ohm of whole and half B&S wire and ribbon sizes for common standard resistance heating alloys. The book also contains calculation equations suitable for use in BASIC programs."